To Other Planets With Upgraded Millennial Kombucha in Rhythms of Sustainability and Health Support - Kozyrovska, Natalia; Reva, Oleg; Podolich, Olga; Kukharenko, Olga; Orlovska, Iryna; Terzova, Vitalia; Zubova, Ganna; Trovatti Uetanabaro, Ana Paula; Góes-Neto, Aristóteles; Azevedo, Vasco; Barh, Debmalya; Verseux, Cyprien; et al. (Frontiers in Astronomy and Space Sciences, 2021)
Humankind has entered a new era of space exploration: settlements on other planetary bodies are foreseen in the near future. Advanced technologies are being developed to support the adaptation to extraterrestrial environments and, with a view on the longer term, to support the viability of an independent economy. Biological processes will likely play a key role and lead to the production of life-support consumables, and other commodities, in a way that is cheaper and more sustainable than exclusively abiotic processes. Microbial communities could be used to sustain the crews’ health as well as for the production of consumables, for waste recycling, and for biomining. They can self-renew with little resources from Earth, be highly productive on a per-volume basis, and be highly versatile—all of which will be critical in planetary outposts. Well-defined, semi-open, and stress-resistant microecosystems are particularly promising. An instance of it is kombucha, known worldwide as a microbial association that produces an eponymous, widespread soft drink that could be valuable for sustaining crews’ health or as a synbiotic (i.e., probiotic and prebiotic) after a rational assemblage of defined probiotic bacteria and yeasts with endemic or engineered cellulose producers. Bacterial cellulose products offer a wide spectrum of possible functions, from leather-like to innovative smart materials during long-term missions and future activities in extraterrestrial settlements. Cellulose production by kombucha is zero-waste and could be linked to bioregenerative life support system (BLSS) loops. Another advantage of kombucha lies in its ability to mobilize inorganic ions from rocks, which may help feed BLSS from local resources. Besides outlining those applications and others, we discuss needs for knowledge and other obstacles, among which is the biosafety of microbial producers.